Epilepsy with Occipital Paroxysms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
A 15 year prospective study of 18 children with benign childhood epilepsy with occipital paroxysms was carried out at the Division of Neurology and Clinical Neurophysiology, King Khalid University Hospital, Riyadh, Saudi Arabia.